Evaluation of the effectiveness of home based or hospital based calisthenic exercises in patients with multiple sclerosis - AYDIN, TEOMAN; AYDIN, TEOMAN; Sariyildiz, M. Akif; GULER, M.; CELEBI, A.; Seyithanoglu, H.; SEYİTHANOĞLU, MEHMET HAKAN; MIRZAYEV, I.; PERU, C.; SEZER, E.; Batmaz, I. (My University, 2014)
OBJECTIVES: The aim of this study is to evaluate the effects of calisthenic exercises on balance, walking speed, fatigue, quality of life, and psychological status in patients with Multiple Sclerosis (MS).